The impact of depression on the quality of life of lung cancer patients undergoing chemotherapy: mediating effects of perceived social support - Xu, Fan; Xie, Shaoju; Li, Qiao; Zhong, Xiaoli; Zhang, Jiquan (Frontiers in Psychiatry, 2025)
BackgroundQuality of life (QOL) in patients undergoing chemotherapy for lung cancer has been a key research area. Numerous studies have examined the relationships among depression, perceived social support (PSS), and QOL. However, the mechanisms underlying PSS in lung cancer patients receiving chemotherapy remain underexplored.ObjectiveTo investigate the mediating role of PSS in the relationship between depression and QOL in lung cancer patients undergoing chemotherapy.MethodsA convenience sample of 390 lung cancer patients undergoing chemotherapy was selected from the outpatient clinics and wards of the Department of Oncology at a tertiary hospital in Deyang City between January 2024 and June 2024. Participants completed a general information questionnaire, Self-Rating Depression Scale (SDS), Multidimensional Scale of Perceived Social Support (MPSSS), and Functional Assessment of Cancer Therapy-Lung Cancer (FACT-L) scale. SPSS 26.0 was used to analyze correlations between depression, PSS, and QOL, while AMOS 26.0 assessed the mediating effect of PSS on the relationship between depression and QOL.ResultsThe mean scores for depression, PSS, and QOL were 39.79 ± 11.63, 68.96 ± 13.09, and 66.43 ± 23.67, respectively. Pearson’s correlation analysis showed that depression was negatively correlated with QOL (r = -0.319, P < 0.001) and positively correlated with PSS (r = -0.484, P < 0.001). Additionally, PSS was positively correlated with QOL (r = 0.349, P < 0.001). PSS partially mediated the relationship between depression and QOL, with a mediating effect value of -0.165, accounting for 50.3% of the total effect.ConclusionDepression in lung cancer patients undergoing chemotherapy directly impacts QOL and indirectly affects it through PSS. Clinically, healthcare providers should address depression in these patients and offer psychological support and interventions as needed. Additionally, medical institutions can implement targeted strategies to help patients build a strong social support system, reduce negative emotions, enhance psychological well-being, and improve overall QOL.